Creative teaching design in STEM: Using graduate learning outcomes to distribute students’ existing knowledge in first-year biology practical work groups - Savage, Julia; Healy, Jillian (Journal of University Teaching and Learning Practice, 2019)
In Australia, a significant number of students enrol in first-year university biology without the benefit of high school biology. In order to help students support each other, the authors of this paper (a central unit academic developer and a biology coordinator of first-year biology) created a classroom activity that facilitated the distribution of the more experienced students of biology throughout the practical work groups. An important feature of this creative design for forming groups, called the GLO Activity in this paper, was the embedding of two of the University’s key teaching and learning priorities within the activity. These were the University’s eight graduate learning outcomes (GLOs) and, inclusive education practice. We discuss creative pedagogies in STEM (Science, Technology, Engineering and Maths) and their link to supporting students in their first year of university study. We explain our scholarly thinking behind the GLO Activity and evaluate its impact. Finally, we reflect on how we, the educators, found satisfaction in thinking deeply to create a new learning structure for a biology practical class that solved one teaching challenge but also met a number of the University’s curriculum principles.